Corporate Digital Communication Framing and Its Impact on Public Trust in the Era of Digital Transformation - Hefri Yodiansyah; Susi Artuti Erda Dewi; Ermairel S (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to analyze the effect of corporate digital communication framing on public trust in the era of digital transformation, with public perception acting as a mediating variable. The research hypothesizes that (1) digital communication framing significantly influences public perception, (2) public perception significantly affects public trust, and (3) framing also has a direct effect on public trust. A quantitative explanatory design was employed using a survey method. Data were collected from 150 respondents in Indonesia who actively use digital media and have been exposed to corporate communication content, selected through purposive sampling. The study measured three main variables—digital communication framing, public perception, and public trust—using Likert-scale questionnaires. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate measurement and structural models. The results reveal that digital communication framing has a significant positive effect on public perception (? = 0.762; p < 0.001), while public perception significantly influences public trust (? = 0.681; p < 0.001). Additionally, framing has a smaller but significant direct effect on public trust (? = 0.245; p < 0.01). Mediation analysis confirms that public perception partially mediates the relationship between framing and trust. These findings imply that effective communication strategies should emphasize not only message delivery but also message framing to enhance credibility and trust. The study contributes to communication theory by integrating framing and the SOR model and provides practical insights for organizations in designing transparent digital communication. This article includes 6 references, 4 tables, 2 figures, and one survey instrument.